The kill order - Dashner, James (New York : Delacorte Press, 2013)
Before wicked was formed, before the Glade was built, before Thomas entered the Maze, sun flares hit the Earth, killing most of the population. Mark and Trina were there when it happened, They survived, but now a virus is spreading. A virus that fills humans with murderous rage. There is no cure or escape. They're convinced that there's a way to save those who are left -- if they can stay alive.
Keywords: Survival -- Fiction; Fantasy fiction